Lexical bundles in selected children’s fiction: A corpus-based analysis / Antermeet Kaur A/P Senthok Singh and Ang Leng Hong - Senthok Singh, Antermeet Kaur; Ang, Leng Hong (Universiti Teknologi MARA, Kedah, 2019)
This study aims to identify four-word lexical bundles in the selected children’s fiction. Previous studies on lexical bundles have investigated the existence of lexical bundles in a wide range of genres. However, little has been done on children’s fiction with regard to the use of lexical bundles in this genre. Using Biber, Conrad and Cortes’s (2004) framework, this study therefore analyses the structural and functional properties of lexical bundles in a corpus of children’s fiction. A 1.7 million-word corpus was built comprising 30 well-read children’s books. The data was generated and analysed using a corpus analysis tool, WordSmith Tools Version 6.0. The results revealed the presence of lexical bundles in the selected children’s fiction. The structural analysis results show that prepositional and verb phrases dominate the children’s fiction. With regard to the functional classification of lexical bundles, referential lexical bundles occur the most, followed by action-related expressions and stance bundles. The results are indicative of the presence of lexical bundles in children’s fiction which has not received much research attention in phraseology studies. This study has several pedagogical implications which stress on the importance of employing lexical bundles in fiction, textbooks and classroom activities in order to benefit children in their language learning and acquisition. Lists of frequent lexical bundles can be incorporated into English language lessons as a way to expose learners to the phraseological patterns of language.